Security Of Dynamic Domain Name System Servers Against DDOS Attacks Using IPTABLE And FAIL2BA: Security Of Dynamic Domain Name System Servers Against DDOS Attacks Using IPTABLE And FAIL2BA - Ibnu Muakhori; Sunardi Sunardi; Abdul Fadlil (Institute of Computer Science (IOCS), 2020)
Availability, integrity and confidentiality are the main objectives of information security and server security. These three elements are links that are interconnected in the concept of information protection.Distributed Denial of Service (DDoS) is an attack to make online services, networks and applications not available by flooding data traffic so that services is unvailable or availability aspects disrupted. This attack resulted in huge losses for institutions and companies engaged in online services and web-based applications being one of the main targets of attackers to carry out DDoS attacks. Countermeasures that take a long time and large recovery costs are a loss for the institution or company that owns the service due to loss of integrity. NDLC (Network Development Life Cycle) is a method that has stages namely analysis, design, simulation, prototyping, implementation, monitoring and management. The NDLC method used aim for the results obtained focused and detailed. Snort IDS applied on the DDNS server functions to record when there is a DDoS attack. Implemention fail2ban as realtime preventation tool on the server by configuring based on the rules applied to fail2ban. The results showed Snort IDS managed to detect DDoS attacks based on the rules applied to Snort IDS. Realtime prevention using Fail2ban successfully functions as a DDoS attack by blocking the attacker's IP Address.